Tax audit adjustments and small and medium-sized corporations (SMCs) characteristics - Siti Aminah, Ahmad Su'ut (2018)
The tax system persists as the primary sources of financing Federal Government developments plans. Malaysia is a country that lagely relies on taxes. Direct taxes administered by Inland Revenue Board of Malaysia (IRBM) accounted for more than two-thirds of the Federal Government revenue in 2015 and income taxes collected from corporate sector was 38% of the federal revenue. This represents the importance of corporate tax collection in generating revenue for the nation. While the annual income tax collection of IRBM shows a positive increment each year, tax non-compliance issues are still ongoing and intensified, evidenced by an increase in the number of cases audited by tax settlement with audit adjustments and penalties. This study was performed to determine whether there was a significant difference in the motivation to conduct tax non-compliance among Malaysian Small and Medium-sized Corporations (SMCs), based on type of industry, size of company, location, and financial liquidity. The study employ quantitative research approach to analyse secondary data of field tax audit cases completed in 2015, obtained from IRBM. The research findings indicate that the type of industry, size of company, location of company and financial liqudity have influenced the probability of SMCs engaging in tax non-compliance behaviour and significant differences exist between them. SMCs engaging in services, construction and manufacturing industries has a high probability of tax non-complinace. Similar with SMCs with total assets exceeding RM10 million and SMCs located in Kelantan/Terengganu, FT Kuala Lumpur/FT Putrajaya and Selangor. SMCs with low liquidity ratio found to be less tax compliant. Therefore, research findings are expected to contribute to the body of literatures and to aid government, tax administrators, and tax practitioners especially on issues relating to SMCs tax compliance behaviour in ensuring the level of voluntary tax compliance is improved.